Vibration emission as a potential source of information for abrasive waterjet quality process control - (:unkn) unknown (SPRINGER LONDON LTD, 2012)
The paper deals with basic research of vibration generated at abrasive waterjet cutting of materials and their analysis of frequency spectrum in the plane cut. As an experimental material, stainless steel AISI 309 has been used. Experimentally controlled factor involved in the experiment was abrasive mass flow rate with values m (a) = 250 and 400 g min(-1) at a constant traverse speed v = 100 mm min(-1). The vibrations were recorded during experimental cutting by sensors PCB IMI type 607A11 placed on experimental material along the cut at a distance of 50 mm from the cutting plane. Data collection was carried by NI PXI measurement system and frequency analyzer Microlog GX-S. Signal was evaluated by virtual instrument created in the object-programming environment LabView 8.5. Various sizes of amplitudes were observed depending on the distance of abrasive waterjet cutting process from the beginning of the cut. Two peaks of frequency bands have been also found: the first between 500 and 600 Hz and the other at approximately 12.5 kHz. Using this method is possible to ensure the determination of technology efficiency of the material removal process.
Keywords: Abrasive waterjet; Abrasive mass flow rate; Traverse speed; Vibration; Frequency spectrum; PREDICTION; SIGNALS; CUT